Gender Justice in Islamic Education: A Study of Parents' Perceptions and Practices in Disanah Village, Indonesia - Rusdiyanto, Rusdiyanto; Inayati, Isna Nurul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2025)
This study examines the implementation of gender justice principles in Islamic education within family contexts in Disanah Village, Indonesia. Using a mixed-methods approach combining surveys (n=83 households) and in-depth interviews, the research explores parental perceptions regarding educational equality between male and female children. The study investigates how Islamic principles related to educational justice are understood and applied at the family level, particularly in rural Indonesian Muslim communities. Through a sequential explanatory design, quantitative data were collected via questionnaires and analyzed using descriptive statistics, followed by qualitative interviews analyzed thematically. The findings reveal that while all respondents (100%) acknowledge their responsibility for children's education, perspectives on equal treatment vary slightly, with 94.04% supporting equal educational opportunities regardless of gender and 5.95% prioritizing children with exceptional abilities. The study concludes that Islamic principles of educational justice are widely understood and valued in the community, though implementation challenges persist. These findings contribute to understanding how religious values can support gender equality in educational settings and offer insights for developing culturally-sensitive approaches to promoting educational equity in Muslim-majority contexts.